Bus Transit Accessibility and Equitability for Vulnerable Populations in Metro Boston, MA: COVID-19 and Beyond - Wilson, Jessica. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Sumeeta Srinivasan.; Committee: Mark Chase.; Keywords: Transportation, Environmental justice, and Urban planning.